KOMUNIKASI PESANTREN DALAM KONSTRUKSI DAN SOSIALISASI SANTRI BEDA BUDAYA DI MA’HAD ALY UIN RADEN INTAN LAMPUNG - Amaliah, Eni (KOMUNIKA, 2018)
The initial process of communication that often occurs in inter-cultural communication, as is done by foreign students in Ma'had Al-Jami'ah is the process of assimilation, namely the acceptance of another culture in a new environment in the form of a system, customs, habits, lifestyle and even language. This is reinforced by the involvement of foreign students in the habits of Indonesian students at Ma’had Al Jami'ah. communication that is often carried out by santri is transactional communication, where interactive communication also occurs but more to the ongoing communication in a relatively long period of time. in the process of intercultural communication that has a different cultural background. For santri immigrants, this is the first step so that the process of intercultural communication runs effectively. And this attitude also aims to assist the adaptation process in an effort to blend in with Indonesian students at Ma’had Al-Jami'ah which will impact on good acceptance by Indonesian students because communication is going well. The use of language in the process of intercultural communication is fundamental, as is the case with the daily activities of foreign students at Ma'had Al-Jami'ah who use Indonesian. Migrants who only understand their local language (their country) when they are in a new environment that has a different language, will not be able to understand the meaning of the message sent by other people in different languages such as Indonesian. By referring to the ethnographic approach of interaction that occurs in communicative activities (Communicative Practices) which consists of communi- cative situations (communicative situations), communicative events (communicative events) and communicative actions the reality of communicative activities found in different cultural students. This can be seen from the pesantren communication which includes Construction and Application of Identity Through Communication Activities, Construction and Implementation of Islamic Boarding Schools Through Communication Situations, Events of Communi-cation and Action Communication, Communication Activities Through Socialization in Pesantren Environment, Communication Activities in Pesantren Education Process.